2014
DOI: 10.1093/arclin/acu020
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Cognitive Impairment After Concussion: Sensitivity of Change From Baseline and Normative Data Methods Using the CogSport/Axon Cognitive Test Battery

Abstract: Concussion-related cognitive impairments are typically evaluated with repeated neuropsychological assessments where post-injury performances are compared with pre-injury baseline data (baseline method). Many cases of concussions, however, are evaluated in the absence of baseline data by comparing post-injury performances with normative data (normative method). This study aimed to compare the sensitivity and specificity of these two methods using the CogSport/Axon test battery. Normative data and reliable chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 39 publications
4
51
1
Order By: Relevance
“…Although prior data on ANAM's performance in the context of SRC is limited, our overall sensitivity rate was consistent with that of one prior report (with false positive rates in our sample somewhat higher; Register-Mihalik, Guskiewicz, et al, 2012). Our sample yielded lower sensitivity but higher specificity than a previously published study of Axon (Louey et al, 2014). …”
Section: Discussioncontrasting
confidence: 77%
“…Although prior data on ANAM's performance in the context of SRC is limited, our overall sensitivity rate was consistent with that of one prior report (with false positive rates in our sample somewhat higher; Register-Mihalik, Guskiewicz, et al, 2012). Our sample yielded lower sensitivity but higher specificity than a previously published study of Axon (Louey et al, 2014). …”
Section: Discussioncontrasting
confidence: 77%
“…Only a single study 13 was published on Axon using average-measure ICC models, and ICCs ranged from 0.83 to 0.93 across the 4 tasks. In this meta-analysis, estimated ESs were different between studies using singlemeasure and average-measure ICC models.…”
Section: Discussionmentioning
confidence: 99%
“…Broglio Although false-positive diagnoses can be a nuisance for athletes, false-negative diagnoses are a bigger concern because they can result in an athlete being returned to play prematurely, leading to further injury or worse. Louey et al 13 reported a false-negative (ie, a concussed athlete being diagnosed as healthy) rate of 17%. When the RCI for a test is high (ie, poor reliability), a high rate of false-negative diagnoses may occur due to the large change in scores needed to identify true change.…”
mentioning
confidence: 99%
“…Previous research has reported that, if performance is evaluated across a cognitive assessment battery (ie, battery approach) rather than through the use of an individual test in isolation (ie, individual subtest approach), it will increase the ability of said battery to detect atypical performance. 27,41,42 Thus, we reevaluated atypical performance for the battery approach using a reliable decrease in performance on 1 + , 2 + , and 3 + subtests using as cutoffs at 95%, 90%, and 80% CIs, respectively. A cutoff of 1 + subtests, the most liberal approach, flagged 53%-69% and 62%-72% of SMs as having atypical performance for the NCG and CNG, respectively.…”
Section: Reliable Changementioning
confidence: 99%
“…26 In contrast, comparisons of individualized baseline data are touted by some as they can account for interindividual variance and have been reported to be more sensitive to changes in postinjury performance. 27 Roebuck-Spencer et al 23 used reliable change (RC) methodology with baseline comparisons to determine meaningful change, as opposed to normal variability in performance, and traditional hypothesis testing to determine statistical significance. The results indicated that SMs with self-reported concussion with active symptoms had statistically significant lower postdeployment scores than controls and concussed SMs without active symptoms.…”
mentioning
confidence: 99%